Exploring Students' Responses: The Feasibility of Pizza Slice Math Learning Media - Hidayati, Yulia Maftuhah; Safitri, Sylviana Ika; Arifin, Achmad Januar; Rahmawati, Syavira Salsabila; Rusnilawati (Jurnal Pedagogi dan Pembelajaran, 2024)
Weaknesses in the learning process are one of the problems that arise in the field of education, especially in mathematics learning. Mathematics learning activities are still dominated by memorization and listening activities. The aim of this study is to identify students' responses to the development of the Android-based learning media, Pizza Slice Math, for teaching fractions in elementary schools. This study uses a qualitative approach to systematically and in detail describe students' responses to the development of the Pizza Slice Math learning media for fractions. Data in this study were collected using a questionnaire technique. The questionnaire used in this study consists of questions aimed at measuring students' responses to the developed learning media. Testing was conducted by administering the learning application to students as respondents. The respondents were 15 second-grade students. The results of testing the Android-based learning application Pizza Slice Math on second-grade students showed a significant improvement in the aspects of content quality and objectives, learning quality, and technical quality after revisions were made. Overall, the application experienced an increase in student ratings, indicating that the application is effective and beneficial in the learning process. This application is recommended for use in learning because it has accurate and complete content quality, provides good learning opportunities, and is easy to use. This indicates that students' responses are very interested in the Pizza Slice Math media. Thus, the Pizza Slice Math application is suitable for use as interactive learning media.